Analysing contractor prequalification criteria in construction: new insights through interpretive structural modelling. (2018) - Goel, Ashish
Previous research has established the importance of selecting suitable prequalification criteria to shortlist competent contractors and the role of these criteria in project success. However, very few studies have dealt with establishing hierarchy and investigating interrelationship among prequalification criteria. The rationale of this research is to unearth this seemingly unapparent relationship among these criteria through interpretive structural modelling (ISM). The analysis reveals that financial capability and past performance of contractor, two of the most commonly used criteria for contractor prequalification, are inadequate for competent contractor short-listing due to their strong dependence on other criteria. Based on the hierarchy developed in the model, it is suggested that criteria like environmental policy, litigation/blacklisting history and bid capacity of the contractor should be given higher importance by the clients. The findings may improve the prequalification process by assisting the clients in making informed decision regarding selection of prequalification criteria based on the hierarchy and classification established in the model.